VIEWS OF UNIVERSITIES AND TERTIARY MATRICULATION EXAMINATION CANDIDATES (UTME) ON FACTORS AFFECTING THEIR CHOICE OF BUSINESS EDUCATION IN NIGERIA - Ibrahim, Adamu; Magaji, Z. B. (Sokoto Educational Review, 2014)
This paper examines the perceived factors affecting the secondary school students’ choice of Business Education in University and Tertiary Matriculation Examination (UTME) in Nigeria. The factors investigated are the profession, nomenclatures of the programme, parents, peer groups, mentors/role model, student’s interest, job prospects and admission intricacy. The study had eight objectives and eight null hypotheses. The design used in the study was descriptive. The researchers distributed two hundred (200) copies of questionnaire to candidates registering for University and Tertiary Matriculation Examination in 2011/2012. Two rating scale structured questionnaire titled UTME Candidates and Business Education (UTMECBE) was the instrument used to gather data from the field for analysis. One hundred and eighty-nine (189) copies of questionnaire were properly filled and subjected to statistical analysis using Statistical Package for Social Science version 16. Chi-square was used to test all the 8 null hypotheses at a significance level of 0.05. The results show, among others that, the teaching profession has a significant effect on student’s choice of Business Education at Universities and Tertiary Matriculation Examination in Nigeria. Based on this, the researcher recommended that government should organise public orientation programme to correct the misconception given to teaching profession (Business Education inclusive) as a programme meant for slow learners and misfits should be corrected.